“For Religion and the Emperor, Death”: Counter-revolutionary Politicization and Independence (Mexico, 1820-1823) - Escrig Rosa, Josep (Hispania Nova, 2022)
The paper studies the mechanisms of counter-revolutionary politicisation during Mexican independence and the First Empire. In this period of transition, the importance of popular mobilisation, whether peaceful or armed, is demonstrated through various documentary sources and the testimonies left by contemporaries. The focus is on the resources used to agitate and mobilise the lower classes of society, taking into account the role of mediators, especially the ecclesiastics. The research is in line with methodological proposals that have highlighted the role of reactionary and anti-liberal phenomena as participants in the change and configuration of modern politics.
Keywords: politicisation; counter-revolution; mexican independence; popular mobilisitation; violence; political-religious propaganda